2022
DOI: 10.1002/ldr.4523
|View full text |Cite
|
Sign up to set email alerts
|

Organic soil amendments and food security: Evidence from Cameroon

Abstract: Food insecurity remains a persistent policy issue in many developing countries. While socio-political, epidemiological, climatic, and productivity-related factors have received attention regarding food insecurity, a rarely considered factor is the changing quality of the soil, a natural resource base that has the potential of increasing or reducing vulnerability to food insecurity. The use of organic soil amendments may be socioeconomically and environmentally advantageous. This study examines the inherent rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Previous empirical analysis (Adams et al, 2020; Adolwa et al, 2019; Nunes et al, 2018; Xiong et al, 2018) found similar results on the positive association between the adoption of soil conservation and yields. In some cases, the adoption of soil conservation practices such as the use of organic soil amendments has been shown to be associated with food security (Tabe‐Ojong, Fabinin, et al, 2022). For the more specific case of Thailand, earlier analysis from this same project area found substantial yield increases because of the farmer participatory research and extension approach (Dalton et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous empirical analysis (Adams et al, 2020; Adolwa et al, 2019; Nunes et al, 2018; Xiong et al, 2018) found similar results on the positive association between the adoption of soil conservation and yields. In some cases, the adoption of soil conservation practices such as the use of organic soil amendments has been shown to be associated with food security (Tabe‐Ojong, Fabinin, et al, 2022). For the more specific case of Thailand, earlier analysis from this same project area found substantial yield increases because of the farmer participatory research and extension approach (Dalton et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond yield and profit increases, adoption of soil conservation could further induce welfare changes given that the benefits of adopting soil conservation are not immediate 1 (Knowler & Bradshaw, 2007; Lapar, 1999; Pannell et al, 2014). The adoption of organic soil amendments, a critical component of soil conservation, has been shown to increase food security (Tabe‐Ojong, Fabinin, et al, 2022). That said, existing studies report significant heterogeneity and context‐dependency, calling for a wider evidence base to improve learning on the relationship between soil conservation and welfare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fallowing refers to keeping a farmland untilled or unsown for some time to allow soil fertility regeneration and other biological functions. Finally, organic soil amendments refer to the use of green and animal manure to improve the fertility of the soil and it has been argued to be important for food security 24 . All these variables are captured as dichotomous variables.…”
Section: Methodsmentioning
confidence: 99%
“…It also represents as aspect of crop diversification which is important for dietary diversity and food consumption 6 . This is also the case for organic soil amendments which is associated with food security 24 . Some of the crops cultivated under intercropping have also been highlighted to contribute to carbon sequestration in many drylands of Africa 25 .…”
Section: Introductionmentioning
confidence: 91%